Decision support needs of kidney transplant candidates regarding the deceased donor waiting list: A qualitative study and conceptual framework. Issue 5 (1st April 2019) - Hart, Allyson; Bruin, Marilyn; Chu, Sauman; Matas, Arthur; Partin, Melissa R.; Israni, Ajay K.
Abstract: Background: Kidney transplant candidates face complex decisions about transplant options such as living donation or acceptance of lower quality kidneys. We sought to characterize knowledge and decision support needs regarding kidney transplant outcomes and options. Methods: We conducted 10 interviews and four focus groups of 28 adult kidney transplant candidates from two centers in Minnesota. Transcripts were analyzed thematically using a grounded theory approach. Results: We identified four themes: First, candidates have a limited understanding of treatment options and demonstrate confusion or a lack of awareness about waiting list outcomes and prognosis. Second, candidates desired frank discussions about likely outcomes and individualized prognosis. Third, emotional barriers impact how patients make informed decisions. Finally, participants relied on the support of family and friends to help process information, and many favored the medical community engaging their family and friends in their medical decisions. These findings were incorporated into a conceptual model to support kidney transplant candidates in medical decision making. Conclusions: Transplant candidates had limited understanding about treatment options and outcomes on the kidney transplant waiting list. Individualized risk information and cognitive approaches that recognize how patients process information and balance competing risks may improve informed decision making.